2018
DOI: 10.17221/490/2018-pse
|View full text |Cite
|
Sign up to set email alerts
|

Crop yields, boron availability and uptake in relation to phosphorus supply in a field experiment

Abstract: The boron (B) availability and uptake were studied in relation to different phosphorus rates applied into soils in a three-year field experiment (2015–2017). The experiment was carried out at the experimental station at Humpolec (Bohemian-Moravian Highlands, Czech Republic). Three rates of phosphorus (20-40-80 kg P/ha) were applied as triple superphosphate. The crop rotation was spring barley-winter oilseed rape-winter wheat. No systematic fertilization with B was used and the response of natural boron soil co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…An interaction between B and P for canola and potato has not been studied earlier to our knowledge, but our results corresponded well with studies where high P supply reduced tissue B concentrations in crops like maize and pea (Yamanouchi 1980, Salinas et al 1986, Chatterjee et al 1990, Günes and Alpaslan 2000. A recent study found a significant positive correlation between B uptake and P supply (most of the P applications are P sufficient) in barley (Mühlbachová et al 2017) but it was found that wheat shoot B concentration was not affected by low P availability. Some reports indicated that P deficiency enhanced the severity of B deficiency in sweet potato, radish and sunflower (Nusbaum 1947, Tanaka 1967.…”
Section: Discussionsupporting
confidence: 91%
“…An interaction between B and P for canola and potato has not been studied earlier to our knowledge, but our results corresponded well with studies where high P supply reduced tissue B concentrations in crops like maize and pea (Yamanouchi 1980, Salinas et al 1986, Chatterjee et al 1990, Günes and Alpaslan 2000. A recent study found a significant positive correlation between B uptake and P supply (most of the P applications are P sufficient) in barley (Mühlbachová et al 2017) but it was found that wheat shoot B concentration was not affected by low P availability. Some reports indicated that P deficiency enhanced the severity of B deficiency in sweet potato, radish and sunflower (Nusbaum 1947, Tanaka 1967.…”
Section: Discussionsupporting
confidence: 91%
“…The trial represents the second part of a three-year field experiment conducted in 2015-2017 at the Humpolec experimental station (Bohemian-Moravian Highlands, Czech Republic, 49.5546239N, 15.3485489E), altitude 525 m a.s.l. The first part of this field trial comprises the effects of increasing doses of phosphorus on boron availability and B-uptake (Mühlbachová et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Boron availability depends on ionic strength, pH, soil biological cycle, humification in soils and also on the association with variety of soil constituents including organic matter content, type and the amount of minerals or formation of colloids; it is also present in adsorbed/exchange forms, occluded in mineral phases (clays and Fe/Al hydroxides) (Matula 2007b, Majidi et al 2010, Kot 2015, Mühlbachová et al 2018. Boron is available for plants as undissociated boric acid, which means that it is complexed in a variety of organic molecules in soil (Hu and Brown 1997).…”
mentioning
confidence: 99%
“…This result is in agreement with [16] who reported that B showed greater performance to leaf-stem, total dry matter weight of plant. Muhlbachova et al [17] have found positive correlation between dry matter yield and B contents in Barley. According to Han et al [18], B deficiency influence plant growth by reducing enzymatic activities and lowering stomatal conductance and CO2 assimilation in plant leaves.…”
Section: Plant Heightmentioning
confidence: 96%